Pakistan-China Partnership to Countering Terrorism: Issues and Challenges - Ahmad, Misbah Nisar; Jathol, Hadia; Munir, Abira (Annals of Human and Social Sciences, 2025)
The partnership of Pakistan and China in combating terrorism offers many benefits, but the challenges are immense. This study, therefore, attempts to probe the dynamics of such a relationship, especially in terms of the kinds of collaborative efforts both nations have invoked as regards strategies and initiatives in response to terrorism. It also looks at the historical context of this particular collaboration-that is, how it came into being and which important events and agreements have determined the nature of partnership in this area-and analyzes how well the two countries have pursued joint counter terrorism measures while identifying shortfalls. Historically, the relationship between Pakistan and China has evolved a strategic partnership through multifaceted cooperation. China and Pakistan have strengthened their teamwork to fight terrorism over the last few decades. In the 1980s and 1990s, they didn’t work together much, but now they have a strong partnership that covers many areas. Both countries worry about the same security issues groups that want to break away or cause trouble in their lands. After the 9/11 attacks, they started working together even more. Big projects like CPEC have made it even more important for them to join forces to stop terrorism and keep the area safe. The areas in which this partnership extends include military cooperation, intelligence sharing, and diplomatic channels of coordination. This paper particularly highlighted areas of cooperation between Pakistan and China to address their growing concerns about terrorism.